A Review on Development of Ceramic-Graphene Based Nanohybrid Composite Systems in Biological Applications - Jakubczak, Michał; Jastrzębska, Agnieszka M. (Frontiers in Chemistry, 2021)
Graphene-based nanocomposites constitute an interesting and promising material for various applications. Intensive progress in the development of this group of materials offers an opportunity to create new systems useful for drinking water decontamination or other biotechnological applications. Nanohybrid structures of graphene-ceramic systems can be obtained using covalent graphene surface modification with nanoparticles (NPs) of ceramic and/or co-deposition of metals with selected morphology and chemistry. The present paper systematizes the associated bio-related knowledge and inspires future development of graphene/NPs systems. Emerging knowledge and unique research techniques are reviewed within designing the required nanocomposite structure and chemical composition, development of new methods of covalent surface modification of graphene with NPs and their optimization as well as analysis of mechanisms governing the formation of covalent bonding. Further, innovative research tools and methodologies are presented regarding the adjustment of functionalities of materials used for the application in drinking water decontamination or biocidal composites. This study provides a comprehensive base for rational development of more complex, hybrid graphene-based nanomaterials with various bio-functionalities that can be further applied in industrial practice.